(untitled) (Bangladesh Journal of Infectious Diseases, 2023)
Background: The spread and adaptation of horseflies to new habitats, driven by global climate change, threatens not only animal health but also human well-being. Objective: This article addresses the significant health risks posed by horseflies, which are known carriers of multiple pathogens causing up to 25 different infectious, parasitic, and viral diseases, including anthrax, tularemia, leptospirosis, and anaplasmosis. Methodology: The study provided an overview based on an extensive literature review from 1929 to 2022, analyzing both Russian and English publications. Results: The 2011 tularemia outbreak in Norway, linked to lemming population surges, and the higher susceptibility among men in Slovakia’s annual tularemia cases highlight the role of animal reservoirs and gender in disease transmission. Leptospirosis, prevalent globally except in cold regions, is influenced by climate events, with significant public health impacts observed in various regions, including Russia and the Philippines following natural disasters. Anaplasmosis, transmitted by insects and ticks and more prevalent in warmer months, remains under-researched, with its rising threat exemplified by the growing ixodes tick population in Belarus. Conclusion: In conclusion, understanding the epidemiology and sources of these diseases, along with recognizing the environmental and anthropogenic factors that influence their transmission, is vital. The study underscores the importance of ongoing surveillance, research, and preventive measures to mitigate the impact of these infectious diseases on public health. Bangladesh Journal of Infectious Diseases, December 2023;10(2):77-84